CPWF Volta V1 Main Message Poster - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Replicating successful agricultural water management interventions in new locations requires consideration of economic, biophysical, institutional, and cultural data. The TAGMI tool offers one way to consider such factors, when targeting agricultural water management interventions.